Patient and treatment delays among Mexican women with breast cancer before and after the Seguro Popular - Rodrigo Huerta-Gutierrez; Efrén Murillo-Zamora; Angélica Ángeles-Llerenas; Carolina Ortega-Olvera; Gabriela Torres-Mejía (Salud Pública de México, 2021)
Objective. To assess whether the Catastrophic Health Expenditures Fund (FPGC, Spanish acronym) was associated with delays in seeking medical care and in starting treatment. Materials and methods. We conducted a before and after cross-sectional study. We included 266 women with breast cancer (BC) diagnosis treated during the last three years before the hospitals received the FPGC and 309 women treated in the following three years after the fund was received by the accredited hospitals. Results. After adjusting for potential confounders, we found no association between the FPGC and delay in seeking medical care or between the FPGC and the treatment delay. Conclusions. The FPGC initiative reduced neither the delay in seeking breast cancer medical care for breast cancer nor the treatment delay.